Nursery Origin and Propagation Stage Influence the Endophytic Fungal Communities Inhabiting Grapevine Planting Stocks - Jadran F. Garcia; Colin Todd; Philippe E. Rolshausen; Dario Cantu (Phytobiomes Journal)
Infection by grapevine trunk disease (GTD) pathogens can occur in nurseries and may result in young vine decline in newly established vineyards. We aimed at profiling the causal agents of GTDs in California nurseries and exploring how the vine propagation processes affect pathogen spread and fungal community dynamics. Plant and environmental samples were collected throughout the plant propagation. For grafted vines, wood tissue samples were collected above the graft union (scion), below the graft union (rootstock), and at the crown (rootstock), and wood necrosis was scored using a 0 to 3 rating system. We used both a metabarcoding approach using PCR primers custom-designed for GTDs and a culturing technique coupled with Sanger sequencing for sample diagnosis. The results showed that mycobiome diversity and composition in vines was significantly influenced by the nursery of origin and the propagation stage. We identified 21 GTD taxa across all plant samples associated with Petri disease, black foot, Botryosphaeria dieback, Phomopsis dieback, and Eutypa dieback. Only 10% of the mother vine cuttings were free of GTD pathogen, but coinfection with multiple pathogens became more frequent as the vines progressed through the propagation pipeline. In particular, the incidence of pathogens associated with Petri disease (Phaeoacremonium, Cadophora, Pleurostoma) and Fusarium increased during that time span, likely because of high contamination levels in soil and water environments. Wood necrosis at the graft union and crown also increased after grafting, and Phaeoacremonium and Fusarium correlated with more necrosis, whereas Trichoderma correlated with healthier wood ratings. Our study suggests that nursery practices strongly influence the GTD pathogen profile. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.